PENGARUH MODEL PEMBELAJARAN VALUE CLARIFICATION TECHNIQUE (VCT) TERHADAP HASIL BELAJAR DAN SIKAP TOLERANSI PADA PEMBELAJARAN PENDIDIKAN PANCASILA SISWA KELAS V SEKOLAH DASAR - Sri Wulandari; Dede Hadiansah; Dadang Suhada (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by the problem of conventional learning models that make students less active so that learning outcomes are low. In addition, the lack of tolerance makes many social values dan attitudes that are the identity of the nation eroded dan began to be replaced by new values. This study aims to improve student learning outcomes dan tolerance attitudes by applying the Value Clarification Technique (VCT) model. This study uses a quantitative research approach with experimental methods dan the research design used is True Experimental in the form of Pretest-Posttest Control Group Design. The population of this study were all UPTD SDN 1 Srengseng fifth grade students in the 2024/2025 academic year. By using random sampling technique. Based on the results of the study obtained the calculation of t test data (Independent sample t-test) learning outcomes thitung 3.215 > ttable (1.592) dan sig (2-tailed) of 0.002 This sig (2-tailed) value < a (0.05) which shows the effe ct of the Value Clarification Technique (VCT) learning model on student learning outcomes. In the tolerance attitude data, the T_hitung value is 7.453> T_table (1.592) dan sig (2-tailed) of 0.00 This sig (2-tailed) value < a (0.05) which shows the influence of students' tolerance attitude by using the Value Clarification Technique (VCT) learning model. Based on the results of data analysis, it can be concluded that there is an effect of the Value Clarification Technique (VCT) learning model on learning outcomes dan tolerance attitudes of grade V students of SDN 1 Srengseng in the 2024/2025 school year.